Academic passion, perceived stress and sleep quality evaluated among medical students of private medical colleges in North Kerala - Francis, Joyal; Aboobacker, Aleena S.; Thomas, Arppana; Mohandas, Bindu (International Journal Of Community Medicine And Public Health, 2023)
Background: Passionate doctors are required for a better health care system. Increased professional and academic requirements increase risk of developing stress and sleep disruption. This study aims to determine the academic passion, stress and sleep quality among medical students and explore the associations among them, which helps to create awareness to improve the mental and physical health of future doctors. Methods: This cross-sectional study among 649 MBBS students was done at 3 private medical colleges in North Kerala during 2019-2020 using a semi-structured 31-item questionnaire containing 4 sections: socio-demographic information, academic passion, perceived stress, and sleep quality. Data collected in 30 minutes from study participants in campus setting was entered in MS excel and analyzed using SPSS-20. Result: A 61.6% were women and 38.4% were men. 48% had chosen the profession because of parental pressure, relatives and friends. 51% were passionate about the medical profession. 69% of students were under high perceived stress (mean PSI score 33.54±8.71 SD). 48% of students were poor sleepers (mean PSQI score 6.11±3.45). A 15.6% of participants relied on medication for sleep at least once a month. Passion showed a significant association with stress (p<0.001) and sleep (p<0.001). Passionate students had less perceived stress and lower sleep quality. Conclusions: Apart from one’s own desire, other factors influenced students to choose MBBS. Only half of the participants were passionate. There is a high prevalence of stress and poor sleep quality among medical students. Passion has an imperative role in one’s life quality.